2003
DOI: 10.1038/sj.bjp.0705271
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent relaxation and endothelial hyperpolarization by P2Y receptor agonists in rat‐isolated mesenteric artery

Abstract: 1 Vasorelaxation and hyperpolarization of endothelial cells by adenosine 5 0 -[b-thio]diphosphate (ADPbS) and adenosine 5 0 -[g-thio]triphosphate (ATPgS) were studied in rat-isolated mesenteric artery. Effects from stimulation of P2X receptors were avoided by desensitization with a,b-methylene adenosine triphosphate. 2 ADPbS caused concentration-and endothelium-dependent relaxations of methoxamineprecontracted small (third generation) and main mesenteric artery. These were inhibited by N o -nitro-L-arginine me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…They observed that in rat mesenteric artery, relaxation of smooth muscle cells and hyperpolarization of endothelial cells caused by the P2Y 2 receptor agonist ATPγS were potentiated in the presence of MRS 2179, an antagonist of P2Y 1 receptors [105], as previously reported in non-splanchnic vessels [27,35,128].…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic supporting
confidence: 72%
See 3 more Smart Citations
“…They observed that in rat mesenteric artery, relaxation of smooth muscle cells and hyperpolarization of endothelial cells caused by the P2Y 2 receptor agonist ATPγS were potentiated in the presence of MRS 2179, an antagonist of P2Y 1 receptors [105], as previously reported in non-splanchnic vessels [27,35,128].…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic supporting
confidence: 72%
“…Finally it may vary dramatically according to the vessel's internal diameter. P2Y 2 receptor-induced EDHF-mediated relaxation was clearly evident in large diameter main branch of the rat mesenteric artery (internal diameter of about 1.24 mm) but almost absent in the rat small mesenteric arteries (internal diameter of about 340 μm) [105]. In another study [172], electrical stimulation or adventitial application of ATP induced endothelium-dependent hyperpolarization in thin hamster mesenteric arteries (internal diameter < 150 μm) but not in thick arteries (internal diameter > 300 μm).…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic mentioning
confidence: 93%
See 2 more Smart Citations
“…This suggests that the relaxation in this condition may be mediated, at least in part, by activation of this subtype of purinergic receptors. It is known that purinergic P2Y receptors may produce vasodilatation in several vascular beds [26,27,28,29,30]. We do not know the endogenous mediator which activates these receptors in our experimental conditions, but it may be ATP.…”
Section: Discussionmentioning
confidence: 85%